141 Q FEVER: A CONTINUING DIAGNOSTIC PROBLEM IN WEST TEXAS AND EASTERN NEW MEXICO. Issue 1 (1st January 2007) - Sehli, S; Shaw, M.; Kimbrough, R. C.; Robinson, M.; Jumper, C.
Abstract : Background: Q fever is a widespread zoonotic infection caused by the pathogen Coxiella burnetii that has both acute and chronic manifestations. Q fever may present as a fever of unknown origin (FUO). We examined three cases of Q fever in west Texas and eastern New Mexico: two chronic and one acute that presented as FUO. Q fever usually occurs following exposure to infected animals. Q fever continues to be a diagnostic possibility in patients with FUO and animal exposure in the southwestern United States. Methods: Cases review from medical records at our institution 2000-2006. Results: Discussion: Q fever may present as an acute or chronic febrile illness, either of which can have nonspecific symptoms and signs. Serologic studies are necessary for the diagnosis. Phase I and phase II serology will differentiate between acute and chronic disease. Although somewhat slow and costly, these studies are key to appropriate diagnosis and therapy. Conclusion: Q fever continues to be a diagnostic problem in west Texas and eastern New Mexico.